Health seeking behavior of street connected children in Addis Ababa, Ethiopia - Zewude, Bewunetu; Siraw, Getahun; Engdawork, Kibur; Tadele, Getnet (Frontiers in Sociology, 2023)
Background Street children are the most neglected segments of the society with limited access to healthcare services. The vulnerability of street children to various health risks has been found by previous studies but little is known about their perceived susceptibility, preventive behavior and illness responses. Hence, the purpose of this study was to identify the health seeking behavior of street children in Addis Ababa. The study focuses on perceived susceptibility to various health risks, sources of health risks, and behaviors pertaining to responding to perceived risks and experienced health problems among the most marginalized groups in Addis Ababa. Methods Using a mixed research approach, quantitative and qualitative data were collected through survey and interview methods from selected street children. SPSS and NVivo software were used to analyze the quantitative and qualitative data, respectively. Results Whereas the street children perceive to be susceptible for ill-health risks related with their living situations, responding to the perceived susceptibility mainly by maintaining personal hygiene and undertaking physical exercises have been identified. The study also revealed that street children were found to be vulnerable for the situations affecting their health and wellbeing mainly due to self-reported engagements in risky behaviors such as smoking cigarette (67.3%), sniffing glue or benzene (68.2%), sharing of personal materials having the potential of transmitting diseases from one person to another (25.5%), and unprotected sexual activities (14.1%). Experiences of visiting healthcare facilities in response to illness symptoms have also constituted an aspect of the health seeking behavior of the street children. Conclusion Awareness of the presence of health risks and perceived susceptibility to the risks promoted both preventive behavior and positive compliance in relation to illness response among children of the street in Addis Ababa.